An Interactive Concave Volume Clipping Method Based on GPU Ray Casting with Boolean Operation - Yuan, Feiniu (Computing and Informatics, 2012)
Volume clipping techniques can display inner structures and avoid difficulties in specifying an appropriate transfer function. We present an interactive concave volume clipping method by implementing both rendering and Boolean operation on GPU. Common analytical convex objects, such as polyhedrons and spheres, are determined by parameters. So it consumes very little video memory to implement concave volume clipping with Boolean operations on GPU. The intersection, subtraction and union operations are implemented on GPU by converting 3D Boolean operation into 1D Boolean operation. To enhance visual effects, a pseudo color based rendering model is proposed and the Phong illumination model is enabled on the clipped surfaces. Users are allowed to select a color scheme from several schemes that are pre-defined or specified by users, to obtain clear views of inner anatomical structures. At last, several experiments were performed on a standard PC with a GeForce FX8600 graphics card. Experimental results show that the three basic Boolean operations are correctly performed, and our approach can freely clip and visualize volumetric datasets at interactive frame rates.